МЕХАНИЗМ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ УСЛУГ ЗДРАВООХРАНЕНИЯ - Kesimov Davron , Bobomurodovich (THE INNOVATION ECONOMY, 2025)
the article reveals features of the provision of medical services and directions of development of mechanisms and levers of the market of medical services in the sphere of health care. At the same time, market relations in health care, which are an integral part of the market of private medical services, are completely resolved, in particular, the growth of utility tariffs, prices for medicines, maintenance of buildings, it is scientifically proven that this is due to the fact that it limits the ability of medical institutions to purchase equipment and consumables, organize meals for patients, carry out preventive measures and treat diseases.